Pengaruh Kegiatan Pengembangan Profesi Terhadap Karier Pustakawan di Universitas Hasanuddin - Darmiati Darmiati; Darmawari Nembo; Sri Junandi (Institut Agama Islam Negeri Salatiga, 2021)
Research purposes is analyze and describe the Effect of Professional Development of Librarians on Career Development of Librarians at Hasanuddin University. This research is quantitative. The research subject is Hasanuddin University librarian. Determination of respondents using purposive sampling method. The number of respondents was 48 civil servant librarians. Collecting data through the distribution of questionnaires and documentation. Descriptive statistical data analysis and multiple linear regression. The study found that partially only the innovative work of librarians affected the career development of librarians at Hasanuddin University. Meanwhile, self-development and scientific publications do not affect the career development of librarians at Hasanuddin University. Then simultaneously self-development, scientific publications and innovative works affect the career development of librarians at Hasanuddin University. Barriers to librarians in professional development are the lack of motivation of librarians; less confident; less focus; ability or knowledge and skills; limited time due to work; less productivity due to environmental factors; limited budget and forum for professional development activities; lack of attention and appreciation from the leadership or agency. Meanwhile, the lack of opportunity and narrow insight is not an obstacle. Furthermore, the obstacles for librarians in career development are lack of strength or ability, feeling satisfied with the position they have, lack of cooperation or a supportive network in their environment. Meanwhile, unsure of the librarian's competence, lack of responsibility such as lazy, likes to be late, often not in the office; lack of strength or ability; lack of information is not obstacle for librarians in career development activities.